Hotel Resort in Chinatown Medan Labuhan Area - Muhammad Juanda; Nelson M Siahaan (Talenta Publisher, 2018)
The development of the historic area in Medan Labuhan requires hotels that meet the standards of domestic and foreign tourists. Tourism development is noteworthy because tourism services include the leading sector in the national economy. As an effort to develop new tourism area, Cultural Heritage Area in Medan Labuhan is a historical tourism area that has the potential to be visited by tourists both domestic and foreign tourists. For this thesis proposed design “Hotel Resort in Chinatown Medan Labuhan Area.” So the resort hotel design approach uses the theme of Vernacular Architecture because the location of the design has an intense relationship with the Heritage Buildings especially Taopekong building. This thing is to reinvigorate the identity of this Chinatown Region like its heyday by making a resort hotel that blends with the old building. The research method used is ethnography method with qualitative data collection. Data collection was obtained from the literature study, field survey, comparative study, and group discussion. So Hotel Resort is the best solution to develop Medan Labuhan Area. With the facilities provided are old building store area, function room, bar & lounge, restaurant, cafe, swimming pool, playground, artificial lake & cottages.